World economy: Restrained trend in 1985 - Günter Großer; Günter Weinert (Intereconomics, 1985)
In 1984 the world economy witnessed the kind of high growth rate it had last seen eight years ago. In the industrialised countries real GNP increased by almost 5%. The most pronounced increase was in the USA, although the initial thrust clearly tailed off during the course of the year. Against this background what are the prospects for the world economy during 1985?
Keywords: 330; Economic Trends